![(x^(22))(x^7)=x^p](https://img.qammunity.org/2023/formulas/mathematics/college/othrypciyv8nddxfwev698p6brflf44elq.png)
In the given expression the base value of the expression are same,
The genral form of base and exponent are given as :
![\begin{gathered} b^a,_{} \\ \text{here b is the base } \\ a\text{ = exponent value} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uqbsq12t11815r0rqewlts9xizyxqla13t.png)
From the properties of base value,
If the base is same then the exponents value will add up,
![x^ax^{b^{}}=x^(a+b)](https://img.qammunity.org/2023/formulas/mathematics/college/p7yjnkpn8qoz8oiyunjzouanv8chvjgeth.png)
Since, we have
![\begin{gathered} (x^(22))(x^7)=x^p \\ \text{ so the exponents value will add up} \\ x^(22+7)=x^p \\ x^(29)=x^p \\ \text{bases are same, so compare the exponents value,} \\ 29=p \\ p=29 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x4mcjgf1jilrrythbew71y4l7uf1ayys7i.png)
So, the value of p is 29.
Answer : p = 29